PENGARUH DAYA TARIK PRODUK PESAING, PERILAKU MENCARI VARIASI TERHADAP LOYALITAS KONSUMEN MELALUI KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA PENGGUNA SMARTPHONE BLACKBERRY - Achmad Ulil Khodlro; Nawazirul Lubis; Bulan Prabawani (Universitas Diponegoro, 2015)
Blackberry smartphone has become a popular brand among people and be the Top Brand in the Top Brand Index (TBI) in Indonesia. The Blackberry’s Top Brand Index is not followed by a good achievement, the Blackberry’s Top Brand Index from 2011 to 2013 is decreasing every year, If the decline is not quickly addressed, the blackberry smartphone brand can be plunge. Right now more and more smartphone brand is distributed in market and most likely will shift the blackberry smartphone’s popularity in Indonesia. This study aims to determine the effect of competitor’s product attractiveness, variety seeking behavior toward consumer loyalty through consumer satisfaction of Blackberry smartphone. This study is included in the explanatory research. Data collection techniques with accidental sampling method with a sample of 100. analyzes conducted qualitatively and quantitatively. Instrumental test using the validity test and reliability test. Quantitative data analysis using crosstab, product moment correlation, simple linear regression coefficient of determination, multiple regression, t test, F test, and path analysis. The results of this study indicate that the competitor’s product attractiveness and variety seeking behavior have significantly negative effect on consumer satisfaction partially and simultaneously, consumer satisfaction has significantly positive effect on consumer loyalty. Based on the path analysis, the independent variable competitor’s product attractiveness have a larger indirect impact on consumer loyalty and variety seeking behavior have a larger direct impact on consumer loyalty.